Total body skeletal muscle mass estimated by magnetic resonance imaging and creatine (methyl-d3) dilution in athletes - Stimpson, S. A.; Miller, R. R.; Barton, M. E.; Leonard, M. S.; Carmichael, O.; van Someren, K. A.; Harridge, S. D. R. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Creatine dilution (D3-cr) is a technique for estimating total skeletal muscle mass (SMM) with practical utility, but has not been applied in athletic populations where body composition may differ to that in the normal population. This study aimed to assess the agreement between SMM derived from both D3-cr and that obtained from whole-body Magnetic Resonance Imaging (MRI) in fifteen male and five female national level kayakers (stature: 182.0 ± 13.1 and 170.0 ± 9.0 cm; body mass: 80.6 ± 9.9 and 66.4 ± 6.0 kg; V?O2peak: 56.5 ± 7.0 and 49.6 ± 4.4 ml•kg-1•min-1, mean±SD). SMM was determined following 60 mg of dosed D3-cr and analysis of expelled urine collected on four subsequent days for creatine, creatinine, D3-cr and D3-creatinine using liquid chromatography/mass spectroscopy. SMM was then estimated by assuming a creatine pool size of 4.3 g/kg. During the same time period a whole-body MRI was undertaken to derive SMM from the analysis of multiple slices taken across the body. A strong positive correlation (F = 74.32; R = 0.90; P < 0.0001) between the two methods was observed, but the D3-cr SMM was found to be significantly higher (43.3 ± 6.8 kg) when compared with MRI (36.3 ± 5.8 kg, p<0.0001). However, the difference between the methods was removed when a higher intramuscular creatine pool (5.1 g/kg) was assumed. These data show that D3-cr has potential utility in athletes, as referenced against MRI, but show that assumptions regarding creatine pool size need to be carefully considered.